Molecular properties of pyruvate bound to lactate dehydrogenase: a Raman spectroscopic study. - Deng, H (1989)
Lactate dehydrogenase (LDH; EC 1.1.1.27) catalyzes the addition of pyruvate to the four position of the nicotinamide ring of bound NAD+; this NAD-pyruvate adduct is bound tightly to the enzyme. We have used the adduct as a model for pyruvate in a competent ternary complex by comparing the Raman spectrum of the bound adduct with that for unliganded pyruvate. To understand the observed normal modes of pyruvate both as the bound adduct and in water, we have taken the Raman spectra of a series of 13C- and 18O-labeled pyruvates. We find that the carboxylate COO- moiety of pyruvate remains unprotonated at LDH's active site and forms an ion pair complex. The frequency of pyruvate's carbonyl C = O moiety shifts from 1710 cm-1 in water downward 34 cm-1 when pyruvate binds to LDH. This frequency shift corresponds to a ca. 34% polarization of the carbonyl bond, indicates a substantial interaction between the C = O group and enzyme, and is direct evidence for and is a measure of enzyme-induced electronic perturbation of the substrate needed for catalysis. This bond polarization is likely brought about by electrostatic interactions between the carbonyl moiety and the protonated imidazole group of His-195 and the guanidino group from Arg-109. We discuss how the data bear on the enzymatic chemistry of LDH.